The Disappearance of Gender Discrimination in Male-dominated Professions: The Career Accounts of Compartmentalizers, Lucky Men and Tough Women - Reid, Erin; Ramarajan, Lakshmi (Organization Science, 2026)
Discrimination against women remains common in male-dominated professions, yet people tend not to acknowledge its impacts for career inequality. Analyzing interviews with 125 journalists, we develop novel theory on how people disappear discrimination in their accounts of their own career progress. Most participants (102/125) regarded gender discrimination to be problematic in the profession. Yet, people were inconsistent in how they explained discrimination’s personal career impacts. Discrimination and advantage slipped in and out of people’s career accounts: some women and men disappeared discrimination by compartmentalizing it from their careers and relying solely on merit to explain their own progress, some men substituted luck for gender advantage as an explanation for progress that could not be explained by merit, and some women centered discrimination-countering practices in their accounts, which simultaneously subverted and disappeared discrimination. Discrimination’s inconsistent presence contrasted with the consistent presence of merit across career accounts. We theorize these contradictions as evidence of an individual-level process of disappearance of gender discrimination, and specify how contextual embeddedness (i.e., close personal relationships and employment structure) shapes people’s accounts. This individual level theory of disappearance of gender discrimination advances scholarship on the disappearance of gender inequality, and also contributes to the growing literature on the intersection of merit and discrimination.